Preparation, structural characterization and health benefits of polysaccharides from Rubus chingii Hu: a review - Shan, Chao; Zhu, Yingjia; Bi, Haizheng; Wang, Xingyu; Wang, Jingyuan; Wang, Meng (Frontiers in Pharmacology, 2025)
Rubus chingii Hu (R. chingii) is a valuable edible and medicinal plant. It contains a variety of surprising active compositions. For example, polysaccharides, phenols, terpenes, organic acids, benzenes, and flavonoids. Among them, polysaccharides, as macromolecular compounds, are receiving increasing attention from researchers. Polysaccharides obtained from R. chingii have anti-tumor, anti-colitis, immunomodulatory, anti-obesity, antioxidant and cytoprotective effects. In this paper, the extraction, purification, structural characteristics and health benefits of R. chingii polysaccharides were reviewed, which laid the knowledge foundation and provided the direction for future research. In addition, the structure-activity relationship of R. chingii polysaccharides was analyzed. Its actual and potential applications in the fields of food, pharmaceuticals, and cosmetics have also been discussed. This provides inspiration for the future research and development of its health products and functional foods. In summary, by reviewing the research on R. chingii polysaccharides in recent years, it will help researchers deepen their understanding of them and facilitate further research on R. chingii polysaccharides.